1998
DOI: 10.1108/03090569810204634
|View full text |Cite
|
Sign up to set email alerts
|

Theory and measurement of consumer innovativeness

Abstract: Presents findings validating French and German versions of the domain specific innovativeness scale or DSI, which was designed to measure consumer innovativeness for a specific product category. The data came from self‐administered surveys of 409 consumers in three countries: the USA (n = 121), Germany (n = 113), and France (n = 175). The study participants completed a questionnaire asking them to describe their wine‐related attitudes and behaviours. Data analysis showed that the DSI was unidimensional, high i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
0
8

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(109 citation statements)
references
References 26 publications
5
96
0
8
Order By: Relevance
“…Consumer innovativeness was measured with four scales borrowed from Goldsmith and Hofacker (1991) and Goldsmith et al (1998). The domain of interest was mobile phones and accordingly subjects were primed with their experience with these products.…”
Section: Methodology Study 1 -Experimental Studymentioning
confidence: 99%
“…Consumer innovativeness was measured with four scales borrowed from Goldsmith and Hofacker (1991) and Goldsmith et al (1998). The domain of interest was mobile phones and accordingly subjects were primed with their experience with these products.…”
Section: Methodology Study 1 -Experimental Studymentioning
confidence: 99%
“…The concept and scaling of domain specific innovativeness (DSI) of Goldsmith and Hofacker (1991) has been found to be associated with the adoption of a wide range of innovations, while its measure, the Domain Specific Innovativeness (DSI) scale, has been shown to be internally and temporally reliable and free of social desirability bias (Goldsmith et al, 1998;Goldsmith and Hofacker, 1991), at least in the populations and situational contexts investigated. Of pertinence here, Goldsmith (2000Goldsmith ( , 2001, Citrin et al (2000), and Blake et al (2003) applied the DSI measure to online shopping.…”
Section: Innovativenessmentioning
confidence: 99%
“…According to previous researches the variables product knowledge, product usage and product involvement as the moderator variables, affect the domain-specific innovativeness in the consumer innovativeness hierarchy model (Girardi, Soutar, & Ward, 2005;Goldsmith, Hauteville, & Flynn, 1998;Grewal, Mehta, & Kardes, 2000) so it is suggested that this subject will be investigated in future researches.…”
Section: Suggestions For Future Researchesmentioning
confidence: 99%